Ethical issues in the planning and the conduct of escape rooms in medical education - Saurabh RamBihariLal Shrivastava; Mayur Wanjari (Wolters Kluwer Medknow Publications, 2024)
Escape rooms in medical education are relatively a novel approach to facilitate critical thinking and decision-making in simulated realistic clinical scenarios among the medical students. The success of escape rooms in the attainment of specified competencies depends on several factors that must be given due consideration for optimizing the overall outcome. Further, there might be multiple ethical concerns that must be given due attention before, during, and after the conduct of such sessions. There is an immense need to integrate ethical considerations while designing and implementing escape rooms in medical schools, as it will aid in the creation of a respectful and encouraging learning atmosphere for the students. In conclusion, escape rooms provide a great learning opportunity for medical students to critically think, engage in teamwork, and learn the art of adaptation depending on the given clinical scenario. However, the successful conduct of such sessions is determined by a wide range of factors, including ethical considerations, and all of them need to be systematically analyzed and measures should be taken to reduce their impact on students.